The Development of Steam-Integrated Textbook in Statistics Materials - Putri, Risma Gita Maharani; Asikin, Mohammad (Universitas Muhammadiyah Surakarta, 2021)
This research aims to develop and determine the quality of integrated mathematics textbook for science, technology, engineering, art, and mathematics (STEAM) in statistics materials. The research method uses the modified Sugiyono development model, including, 1) potential dan problems; 2) data collection; 3) product design; 4) design validation; 5) product test (readability test); and 6) the final product. The data were collected by a questionnaire and a readability test. To determine the practicality of the textbook, the questionnaire was validated by six experts while the readability test was given to students. The result showed that the teaching materials were valid with a validity test percentage of 88,99% and a readability test percentage of 80,62%. Thus, integrated textbook for STEAM are of high quality because they meet the suitability of characteristics, valid to use, and are practical or easily understood by students.